The role of political parties in the election of deputies Parliament of the Republic of Kazakhstan - Amandykova, S.K.; Bukalerova, L.; Korpebayev, Zh. (Bulletin of the Karaganda University “Law Series”, 2020)
The article is devoted to the participation of political parties in the elections of deputies of the Parliament of the Republic of Kazakhstan, including deputies of the Mazhilis of the Parliament of the Republic of Kazakhstan. The role of political parties as an institution of representative democracy, which is expressed in the representation of the opinion of the people in the legislative branch of power, is substantiated. In the process of research, the laws were studied: the constitutional law of the Republic of Kazakhstan «On Elections in the Republic of Kazakhstan», the laws of the Republic of Kazakhstan «On Political Parties». The analysis of the activities of political parties of the Republic of Kazakhstan and foreign countries through an in-depth study of laws and practice. A study of the practice of legal regulation and the participation of political parties in legislative elections in foreign countries shows the limited approaches used in Kazakhstani legislation to create favorable conditions for the establishment of a multi-party system, to involve the widest sections of the population in political activity and to participate in the elections of deputies of the Parliament of the Republic of Kazakhstan. Features of the proportional electoral system of the system that are used in the election of deputies of the Mazhilis of the Parliament of the Republic of Kazakhstan were identified. The article shows the processes of a gradual transition from a majoritarian electoral system to a proportional system, which allowed political parties in Kazakhstan and a number of foreign countries to actively participate in the process of election of deputies. When writing the article, the authors used general methods of scientific knowledge: synthesis and analysis, induction, deduction, modeling, which made it possible to comprehensively consider the studied constitutional and legal phenomena. The methods of comparative legal, systemic, logical and statistical were also applied.